Hormone replacement therapy prevents bone loss in patients with inflammatory bowel disease. - Clements, D (1993)
Patients with inflammatory bowel disease have an increased prevalence of osteoporosis, and suffer high rates of spinal bone loss. Hormone replacement therapy (HRT) is effective in the treatment and prevention of osteoporosis but has not been studied in patients with inflammatory bowel disease. A two year prospective study of HRT in inflammatory bowel disease was performed in 47 postmenopausal women aged 44 to 67 years with ulcerative colitis (25) or Crohn's disease (22). Patients had radial and spinal bone density measured annually by single photon absorptiometry and quantitative computed tomography respectively. The mean (95% confidence intervals) annual change in radial bone density was +1.42%/yr (+0.58 to +2.26; P < 0.005) and for spinal bone +2.60%/yr (+1.06 to +4.15; p < 0.005). There was no significant correlation between rates of change of bone density at the two sites, or between the rates of change and the initial bone density either in the radius or spine. Twelve patients were given prednisolone during the study, and their rates of change for spinal bone density were lower, but values were not statistically significantly different from those who did not receive corticosteroids. Changes in bone density for patients with ulcerative colitis and Crohn's disease were not significantly different. The change in bone density did not correlate with the patients' age or number of years after the menopause. It is concluded that HRT is effective in prevention of bone loss in postmenopausal women with inflammatory bowel disease.